Acute Kidney Injury Secondary to Hypothyroidism-Induced Rhabdomyolysis - Ulu, Ramazan; Gozel, Nevzat; Yigit, Irem Pembegul; Gurel, Ali; Dogukan, Ayhan (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2016)
Acute renal impairment due to rhabdomyolysis in patients with hypothyroidism is quite rare. We describe a case of acute kidney injury due to hypothyroidism-induced rhabdomyolysis in a 47-year-old man who was under levothyroxine medication. Physical and laboratory findings were consistent with hypothyroidism, acute kidney injury, and rhabdomyolysis. Laboratory findings showed acute kidney injury, rhabdomyolysis and hypothyroidism. There was no obvious factor causing rhabdomyolysis except hypothyroidism.
Hipotroidiye Bagli Kas Yikimi Sonrasi Gelisen Akut Böbrek Hasar
Keywords: Hypothyroidism; Rhabdomyolysis; Acute kidney injury